2019
DOI: 10.7150/ijbs.29323
|View full text |Cite
|
Sign up to set email alerts
|

Sirt6 Suppresses High Glucose-Induced Mitochondrial Dysfunction and Apoptosis in Podocytes through AMPK Activation

Abstract: Previous studies have shown that mitochondrial dysfunction plays an important role in high- glucose(HG)-induced podocyte injury and thus contributes to the progression of diabetic nephropathy(DN). The histone deacetylase Sirtuin6 (Sirt6) has been revealed to have an essential role in the regulation of mitochondrial function in skeletal muscle and cardiomyocytes. However, its specific role in mitochondrial homeostasis in podocytes is undetermined. Here, we aimeds to explore the physiological function of Sirt6 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 42 publications
4
82
0
Order By: Relevance
“…65 Moreover, recent studies showed that SIRT6-mediated AMPK activation reduced mitochondrial dysfunction in either high-glucose-cultured podocytes or glycochenodeoxycholate-pretreated biliary epithelial cells. 66,67 Our results showed that SIRT6 and AMPK-PGC-1α-AKT signaling were further inhibited by diabetic MI/R injury. Long-term melatonin administration reduced the vulnerability of diabetic heart toward MI/R injury by preserving mitochondrial quality control and activating SIRT6 and AMPK-PGC-1α-AKT signaling.…”
Section: F I G U R E 1mentioning
confidence: 70%
“…65 Moreover, recent studies showed that SIRT6-mediated AMPK activation reduced mitochondrial dysfunction in either high-glucose-cultured podocytes or glycochenodeoxycholate-pretreated biliary epithelial cells. 66,67 Our results showed that SIRT6 and AMPK-PGC-1α-AKT signaling were further inhibited by diabetic MI/R injury. Long-term melatonin administration reduced the vulnerability of diabetic heart toward MI/R injury by preserving mitochondrial quality control and activating SIRT6 and AMPK-PGC-1α-AKT signaling.…”
Section: F I G U R E 1mentioning
confidence: 70%
“…2b). Recent studies have also found that Sirt6 protects mitochondria of podocytes and exerts antiapoptotic effects via activation of the AMP-activated protein kinase (AMPK) pathway [52]. Collectively, pharmacological targeting of Sirt6-mediated Notch signaling pathways at multiple levels may provide a novel approach for the treatment of proteinuric kidney disease.…”
Section: Nad + -Dependent Deacetylases On the Regulation Of Podocytementioning
confidence: 99%
“…SIRT6 plays an important role in DNA repair and maintenance of genome stability, Participating in various physiological regulation mechanisms such as cell proliferation, differentiation and aging ( Gertler and Cohen, 2013 ), Recent studies have shown that SIRT6 can up-regulate AMP/ATP, then activate AMPK/Fox O3, Exerting antioxidant stress effect ( Wang et al., 2016 ), Fan et al. observed that overexpression of Sirt6 can increase AMPK phosphorylation level, The apoptosis of podocyte induced by HG was reduced ( Fan et al., 2019 ).At the same time, some studies have revealed that SIRT6 overexpression can inhibit senescence and apoptosis of nucleus pulposus cells by inducing autophagy ( Chen et al., 2018 ). Some studies pointed out that AMPK activity in aged and aging hearts is significantly reduced compared with young hearts, AMPK is an important regulatory kinase upstream of myocardial m TOR, which can inhibit the kinase activity of mTOR and activate autophagy to protect myocardium ( Ma et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%